Prinsip Habluminallah dalam Puisi “Sajadah Panjang” Karya Taufik Ismail, dan “Tuhan, Kita Begitu Dekat” Karya Abdul Hadi WM - Istiqomah Dinda Rahmawati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to describe the principle of habluminallah in poetry. The objects of study in this research are the poems "Long Sajadah" by Taufik Ismail and "God, We Are So Close" by Abdul Hadi WM. The method used in presenting the results of the analysis is a qualitative descriptive method. The researcher conducted a literature search of the two poems to collect research data which was then carried out in comparative literature. The approach taken is objective, namely finding something unique in poetry. The data discussed in this study: (1) Analysis of the intrinsic narrative elements of the two poems (2) the principle of habluminallah in both poems. The results of the study show that the poem "Long Prayer Prayer" by Taufik Ismail and the poem "God, We Are So Close" by Abdul Hadi WM have a connection, because the two poems explain religious values, namely the close relationship between humans and their gods.